The grand design : from common market to atlantic partnership - Kraft, Joseph (New York : Harper and Brothers Publisher, 1962)
The principle of Atlantic partnership, its implications and effects on European integrations as it touches the industrialized and underdeveloped nations.
SJU 22/01/2019
Loans